Collaboration in Cognitive-Behavioural Counselling: A Case Example - Merali, Noorfarah; Lynch, Patrick (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper describes the use of collaborative empiricism in Cognitive-Behavioural Counselling. While some people view clients of Cognitive-Behavioural Counsellors to be passive recipients of interventions, counsellor-client collaboration is an integral aspect of the conceptualization of humans as active beings. This is a fundamental tenet of Cognitive Behavioural approaches. The case of a 73-year-old male client presenting with panic attacks is used to illustrate the importance of counsellor-client collaboration in promoting the selection of appropriate interventions and in facilitating client engagement in the counselling process. The use of investigative record-keeping assisted the counsellor and client in this case to gather baseline information about the panic attacks, and provided clues about contextual triggers and appropriate solutions.